Racism, Cultural Taxation and the Role of an Indigenous Teacher in Rural Schools - Hogarth, Melitta Dorn (Australian and International Journal of Rural Education, 2019)
The underrepresentation of Indigenous teachers within Australian schools was made evident in the most recent More Aboriginal and Torres Strait Islander Teachers Initiative (MATSITI) project (Johnson, Cherednichenko, & Rose, 2016). The shortfall of Aboriginal and Torres Strait Islander teachers had been initially identified back in 1975 with the Schools Commission Report (Schools Commission, 1975). The challenge was set by Hughes and Willmot in 1982 to have 1000 trained Indigenous teachers by 1990 within the schooling sector (Hughes & Willmot, 1982). The lack of representation of Indigenous teachers is just one part of the story. In this paper, I share my lived experiences as an Aboriginal classroom teacher in rural schools throughout Queensland. Using an ethnographic narrative approach, I give insight to the realities of the Indigenous classroom teacher in rural schools. In turn, I address some of the inherent institutionalised racism apparent, the assumptions held by others, and the consequential demands placed on the Indigenous teacher. The stories shared are my own and do not insinuate that all other Indigenous teachers have had the same experience. However, by sharing my story, the purpose of this paper is to open dialogue about the role of Indigenous teachers in rural schools and to make schools aware of how they position these rare commodities they have on staff.